ANALISIS PENGARUH PENDAPATAN ASLI DAERAH (PAD) TERHADAP REALISASI PELAYANAN PUBLIK DI PROVINSI SUMATERA SELATAN - Chitra Imelda (Fakultas Ilmu Sosial dan Ilmu Politik, 2022)
Local revenue (PAD) in South Sumatra Province is optimally pursued to carry out effective and efficient functions to improve the quality of public service management. As one of the sources of financing owned by the region, regional original income (PAD) is income obtained by the local government level (Pemda) which is extracted by the regional government from economic sources in the area. Based on PAD (Regional Original Income) sourced from local tax revenues, tax revenue in South Sumatra Province up to the first quarter of 2021 amounted to IDR 2.00 trillion. This revenue realization decreased by IDR 177.77 billion. Therefore, it is necessary to increase public services to the community so that they become an important element, bearing in mind that the payment of taxes and fees is already a public obligation to the State.